Pencerahan Hukum Kepada Masyarakat Desa Rotnama - Yeheskel Wessy; Stelvia W. Noya; Micael Ririhena (Pemberdayaan Masyarakat : Jurnal Aksi Sosial, 2024)
Criminal law is a branch of law that regulates crimes and violations and the sanctions that can be imposed on perpetrators. A good understanding of criminal law is very important for society to be able to avoid acts that violate the law and understand their rights and obligations as citizens. Criminal law is a collection of rules that determine what actions are prohibited and subject to criminal sanctions. Actions that are categorized as criminal acts can include crimes and violations. Regarding this matter, it is deemed necessary by the Rotnama Village Government, Mdonahiera District, Southwest Maluku Regency to schedule it as a form of cooperation in implementing service to the Rotnama Village Community through socialization with the theme "Bacarita with the Rotnama Village Community" which in principle provides legal understanding and builds legal awareness to Rotnama Village community regarding various legal problems that occur and forms of resolution. The implementation of community service activities is carried out by the Lecturer Team at the request of the Head of Rotnama Village to collaborate in implementing community service activities for the Rotnama Village Community in order to provide an understanding of criminal law which is very important for every member of the community. By understanding criminal law, people can contribute to creating a safe and orderly environment and ensure that their rights are protected by law